Volí diabetologové terapii racionálně? Základní výsledky projektu PROROK (Prospektivní observační projekt významu diference glykemie nalačno a postprandiální glykemie pro odhad úspěšnosti terapie diabetu 2. typu) - Žďarská, Denisa Janíčková; Piťhová, Pavlína; Pavlík, Tomáš; Kvapil, Milan (Vnitrni lekarstvi, 2015)
INTRODUCTION: The PROROK project (A prospective observation project to assess the relevance of the difference between fasting glycemia and postprandial glycemia to estimation of success of type 2 diabetes therapy) had a character of a non-interventional, prospective, multicentric observation project conducted for a period of 6 months, whose aim was to quantify the relevance of the difference between fasting and postprandial glycemia to the success of GLP1 receptor agonist treatment, or insulin therapy with basal or premixed insulin, or a combination of basal and bolus insulin. Physicians chose therapy for inadequately compensated patients at their own discretion, with 4 972 patients included. AIM: The study aimed at the assessment of the differences in basic anthropometric and biochemical parameters between the patient cohorts included in the PROROK project with regard to the therapy selected by the treating diabetologist. METHODOLOGY AND RESULTS: The patients treated with GLP1 receptor agonists were quite young, they have suffered from diabetes for a shorter period of time and at the same time were more obese and had the highest concentration of triacylglycerols. The patients who underwent basal insulin therapy, had the highest fasting glycemia. The patients for whom premixed insulin therapy or basal/bolus insulin regimen were chosen, manifested the highest postprandial glycemia, those with basal/bolus insulin regimen had the highest initial glycated haemoglobin. The difference between fasting and postprandial glycemia was the smallest in the cohort for which basal insulin therapy was chosen and the greatest in the cohort chosen for the therapy with premixed insulin, or with the basal/bolus insulin combination. Average improvement in glycated haemoglobin values reached 1.6 % within the whole cohort, a median of the resulting glycated haemoglobin reached 5.9 % or 5.8 % (GLP1 receptor agonist treatment). All the differences amounted to p < 0.001. CONCLUSION: Bearing in mind that the differences established in the parameters describing the cohorts, although statistically relevant, are of smaller clinical relevance, we regard as an important finding that the choice of therapy is in accordance with the basic knowledge about the pathophysiology of type 2 diabetes and possibilities of an individually chosen targeted intervention with antidiabetic therapy. We may conclude that most of the physicians participating in the PROROK project choose their therapy in a rational manner.
Keywords: Female; ženské pohlaví; Diabetes Mellitus, Type 2; dlouhodobě působící inzulin; lidé; Blood Glucose; postprandiální období; Hypoglycemic Agents; receptory glukagonu; diabetes mellitus 2. typu; Insulin; Glycated Hemoglobin A; omezení příjmu potravy; hypoglykemika; prospektivní studie; Male; Receptors, Glucagon; Prospective Studies; glykovaný hemoglobin; receptor pro glukagonu podobný peptid 1; Postprandial Period; Insulin, Long-Acting; lidé středního věku; Glucagon-Like Peptide-1 Receptor; mužské pohlaví; Fasting; inzulin; krevní glukóza; Glycated Hemoglobin; Middle Aged; Humans